THE OCCURRENCE OF CONTRACTURE AND THE SEVERITY OF BURN INJURIES AMONG BURN PATIENTS TREATED AT DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA (2020-2022) - Gifta Marshanda Qanitah Hamiseno; Iswinarno Doso Saputro; Diah Mira Indramaya; Lobredia Zarasade (Jurnal Rekonstruksi dan Estetik)
Highlights: